Pelletisation Behavior of Fluxed Iron Ore Pellets of Varying Basicities Made with Waste Fines - Alok Sarkar; Arup Kumar Mandal; O. P. Sinha (International Journal of Science and Engineering, 2013)
The present study deals with the utilization of fines generated from comminution process (crushing, grinding and screening) of the Run of Mines into value added products i.e. fluxed iron ore pellets. The study comprises to understand the physical and mechanical behavior of five distinguished chemical compositions of green and dried iron ore pellets with respect to a typical Mini Blast furnace (MBF) burden data and furnace operating parameter. The maximum basicity of pellets was calculated 2.37 to make slag neutral when blast furnace runs at 100% high ash coke (avg. ash content= 29%). The crushing strength and drop number of various green pellets were measured. Green Crushing Strength was decreased with increasing lime fines. The addition of lime fines as a burnt lime, which has acicular structure creates less plasticity and brittle like fracture occurred. Due to formation of hard CaCO3 layer on the surface, after increasing lime contain crushing strength was increased in the air and oven dry pellets with respect to acid pellet (0% lime fines addition). [How to cite this article: Sarkar, A., Mandal, A.K., and Sinha, O.P. (2013) Pelletisation Behavior of Fluxed Iron Ore Pellets of Varying Basicities Made with Waste Fines. International Journal of Science and Engineering, 5(2),9-14. Doi: 10.12777/ijse.5.2.9-14]